The 2-Domination Number in Interval-Valued Fuzzy Graphs - Nooraldeen .O. AL-saklady; Mahioub .M. Q. Shubatah (IJRDO -JOURNAL OF MATHEMATICS, 2020)
In this paper we focus on 2- domination number of an intervalvalued fuzzy graphs G by using effective edge and is denoted by γ2(G) and obtain some results on γ2(G), the relationship between γ2(G) and some other, known parameters concepts are obtained. Finally the domatic number of interval-valued fuzzy graph is introduced further some results on this concept are investigated.